Motivations and Attitudes Affecting High School Students' Choice of Foreign Language - Stewart-Strobelt, Jody; Chen, Huabin (Adolescence, 2003)
Study explored the motivations for students' choice of foreign languages. As long as foreign language study is elective in high schools, and as long as a variety of languages are offered, students' motivation will remain important for foreign language educators, especially in schools where various language programs compete with one another for student enrollments and the programs' ultimate survival. (Contains 4 tables.) (ADT)